Prognostic impact of initial platelet count and post-induction platelet recovery in elderly AML patients: associated with circulating cytokines - Chun Ling; Chun Ling; Neng-Neng Cao; Xiao-Wei Niu; Shi-Yun Xu; Wen-Yu Gong; Wen-Qiang Bao; Qi-Chuan Jin; Yin Wang; Jing Wu; Chang-Zhi Zhao; Wen-Jing Fu; et al. (Frontiers in Oncology)
ObjectiveAcute myeloid leukemia (AML) is a highly heterogeneous hematologic malignancy, with various clinical features influencing its prognosis. The aim of this study to evaluate the impact of platelet count at diagnosis and platelet recovery after induction chemotherapy on the survival outcomes of elderly AML patients.MethodsA total of 109 elderly patients with AML who were treated in our center between 2017 and 2023 were evaluated. According to the median platelet counts at the time of new diagnosis, the cases were divided into a low platelet counts group (≤40×109/L, n=54) and a high platelet count group (>40×109/L, n=55). Platelet recovery times were accepted as the periods from the beginning of induction chemotherapy to a platelet count of ≥20×109/L 3 days in a row, respectively. The median time to platelet recovery was 25 days (range12-47) for all patients. Therefore, platelet recovery in the first 25 days was defined as early platelet recovery and at >25 days it was defined as late platelet recovery.ResultsLow platelet counts at diagnosis and early recovery of platelet counts after induction therapy indicate longer overall survival (OS) and Leukemia-free survival (LFS). Patients with high platelet counts at diagnosis and those with delayed platelet recovery after induction therapy exhibited elevated levels of interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α). Additionally, patients with high platelet counts at diagnosis also had relatively higher levels of interleukin-8 (IL-8).ConclusionPlatelets can be used as a prognostic biomarker for elderly AML and may be associated with circulating cytokines.